I have to figure out what the person did wrong and correct it)) AB=√(6-2)² + [1-(-4)]² = √4² +5² =√16+25 = √41​

I have to figure out what the person did wrong and correct it))
AB=√(6-2)² + [1-(-4)]² = √4² +5² =√16+25 = √41​

1 thought on “I have to figure out what the person did wrong and correct it)) AB=√(6-2)² + [1-(-4)]² = √4² +5² =√16+25 = √41​”

  1. Step-by-step explanation:
    I assume the square root always goes across the whole expression, right ?
    the calculation you provided is correct. there was nothing done wrong here.
    so, I guess the mistake must have been made with the coordinate numbers in the first place.
    since I don’t see any graphic or the coordinates of the points, where clearly the distance has to be calculated, I cannot give you the details.
    based on the calculation, the points would have been
    A (2, -4)
    B (6, 1)
    and I guess the original coordinates must be different somehow.
    otherwise it would all be correct.

    Reply

Leave a Comment